Magnetic Nanoparticle-Mediated Orientation of Collagen Hydrogels for Engineering of Tendon-Mimetic Constructs - Wright, Abigail L.; Righelli, Lucrezia; Broomhall, T. J.; Lamont, Hannah C.; El Haj, Alicia J. (Frontiers in Bioengineering and Biotechnology, 2022)
Despite the high incidence of tendon injuries worldwide, an optimal treatment strategy has yet to be defined. A key challenge for tendon repair is the alignment of the repaired matrix into orientations which provide maximal mechanical strength. Using oriented implants for tissue growth combined with either exogenous or endogenous stem cells may provide a solution. Previous research has shown how oriented fiber-like structures within 3D scaffolds can provide a framework for organized extracellular matrix deposition. In this article, we present our data on the remote magnetic alignment of collagen hydrogels which facilitates long-term collagen orientation. Magnetic nanoparticles (MNPs) at varying concentrations can be contained within collagen hydrogels. Our data show how, in response to the magnetic field lines, MNPs align and form string-like structures orientating at 90 degrees from the applied magnetic field from our device. This can be visualized by light and fluorescence microscopy, and it persists for 21 days post-application of the magnetic field. Confocal microscopy demonstrates the anisotropic macroscale structure of MNP-laden collagen gels subjected to a magnetic field, compared to gels without MNP dosing. Matrix fibrillation was compared between non- and biofunctionalized MNP hydrogels, and different gels dosed with varying MNP concentrations. Human adipose stem cells (hASCs) seeded within the magnetically aligned gels were observed to align in parallel to MNP and collagen orientation 7 days post-application of the magnetic field. hASCs seeded in isotropic gels were randomly organized. Tenocyte-likeness of the cells 7 days post-seeding in collagen I scaffolds was confirmed by the positive expression of tenomodulin and scleraxis proteins. To summarize, we have developed a convenient, non-invasive protocol to control the collagen I hydrogel architecture. Through the presence or absence of MNP dosing and a magnetic field, collagen can be remotely aligned or randomly organized, respectively, in situ. Tendon-like cells were observed to organize in parallel to unidirectionally aligned collagen fibers and polydirectionally in non-aligned collagen constructs. In this way, we were able to engineer the constructs emulating a physiologically and pathologically relevant tendon niche. This can be considered as an innovative approach particularly useful in tissue engineering or organ-on-a-chip applications for remotely controlling collagen matrix organization to recapitulate the native tendon.